1998
DOI: 10.1530/eje.0.1390198
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between leptin and oestrogens in healthy women

Abstract: Objective: Leptin, a protein secreted by white adipocytes, plays a relevant role in the regulation of body weight and food intake. A possible role for sex hormones in the regulation of leptin secretion has been suggested; however, the effect of variations in oestrogen concentration on serum leptin levels has not been described so far. Methods: In study 1, serum leptin concentrations were measured on days 3, 10, 17 and 24 of the menstrual cycle in 18 healthy, lean, regularly menstruating women, aged 18-35 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
2
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 22 publications
5
55
2
3
Order By: Relevance
“…We found a statistically significant correlation between serum oestradiol and leptin when measurements from different time points were pooled together, which is in agreement with one earlier report (24) but not with others (25)(26)(27)(28). This weak positive correlation between serum leptin and oestradiol concentrations could not be reproduced when the percentage changes in these variables were used in the analysis.…”
Section: Discussionsupporting
confidence: 90%
“…We found a statistically significant correlation between serum oestradiol and leptin when measurements from different time points were pooled together, which is in agreement with one earlier report (24) but not with others (25)(26)(27)(28). This weak positive correlation between serum leptin and oestradiol concentrations could not be reproduced when the percentage changes in these variables were used in the analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Results published on serum leptin levels during the physiological menstrual cycle vary considerably. Some studies showed significant increase in the late follicular phase (9,10), and some did so on the day of the onset of the luteinising hormone (LH) surge (11,12). Other investigations described significant increase in serum leptin levels in the late luteal phase (13)(14)(15)(16)(17), and again others reported only small, not statistically significant variations during the menstrual cycle (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…During the menstrual cycle leptin levels increase in the follicular phase and decline in the luteal phase (Hardie et al 1997), suggesting a disproportional influence of estradiol elevation on leptin secretion (Mannuci et al 1998, Riad-Gabriel et al 1998. During IVF cycles, serum leptin rises in response to exogenous follicle-stimulating hormone (FSH) administration (Butzow et al 1999).…”
Section: Introductionmentioning
confidence: 99%